Business Development Strategies for EG Group - Ambarwati, Nurita; Indrawan, Raden Dikky; Ekananta, Arry (Indonesian Journal of Multidisciplinary Science, 2023)
EG Group is one of the wedding vendors in the area of Bogor City, which encompasses Kresna Tenda, Kresna Decoration, and Jeima Bridal. This research aims to analyze the macro and micro external factors of EG Group, analyze the internal factors of EG Group based on the distant environment and industry environment, and formulate appropriate strategies to be implemented by EG Group. The research was conducted in January 2023 - April 2023. The research was carried out at the EG Group office located at Jalan Kresna Raya No. 10 Indraprasta, North Bogor. The research findings are as follows: (1) External factors include the need of the community for holding wedding celebrations and changing wedding trends, (2) Internal strategic factors of the company include the merger that enables collaboration in the financial needs of the company and the limited scope of business which is confined to Bogor City, and (3) SWOT analysis reveals seven alternative business development strategies for EG Group, which include leveraging the benefits of the merger to improve efficiency and diversification, utilizing available capital to enhance branding and improving services by optimizing human resources, expanding the range of decoration and wedding attire services to meet the needs of the community, utilizing positive relationships to drive performance improvement, maximizing the capabilities of existing resources to compete in the wedding industry, forming an R&D team to innovate in response to changing trends, and expanding the business scope.